FRACTIONATION OF THE NOBLE METALS BY PHYSICAL PROCESSES - Ballhaus C.; Bockrath C.; Wohlgemuth-Ueberwasser C.; Laurenz V.; Berndt J. (My University, 2006)
During partial melting in the earth's mantle, the noble metals become fractionated. Os, Ir, Ru, and Rh tend to remain in the mantle residue whereas Pt, Pd, and Re behave mildly incompatible and are sequestered to the silicate melt. There is consensus that sulfide plays a role in the fractionation process; the major noble metal repository in the mantle is sulfide, and most primitive mantle melts are sulfide-saturated when they leave their mantle sources. However, with sulfide-silicate partitioning, the fractionation cannot be modeled properly. All sulfide-silicate partition coefficients are so extremely high that a silicate melt segregating from a mantle source with residual sulfide should be largely platinum-group elements free. We offer a physical alternative to sulfide-silicate chemical partitioning and provide a mechanism of generating a noble metal-rich melt from a sulfide-saturated source: Because sulfide is at least partially molten at asthenospheric temperature, it will behave physically incompatible during melt segregation, and a silicate melt segregating from a mantle residue will entrain molten residual sulfide in suspension and incorporate it in the basaltic pool melt. The noble metal abundances of a basalt then become independent of sulfide-silicate chemical partitioning. They reflect the noble metal abundances in the drained sulfide fraction as well as the total amount of sulfide entrained. Contrary to convention, we suggest that a fertile, sulfide-rich mantle source has more potential to generate a noble metal-enriched basaltic melt than a refractory mantle source depleted by previous partial melting events. © Springer-Verlag 2006.